FORAGE YIELD AND NUTRITIONAL QUALITY OF PEARL MILLET GENOTYPES AS HAY AND SILAGE IN MEDITERRANEAN CONDITIONS - Cemal DENIZ; Tahir Polat; Celal YÜCEL (Journal of Animal and Plant Sciences, 2026)
Pearl millet Pennisetum glaucum (L.) R. Br.] exhibits drought tolerance and is increasingly used as essential feed. Nevertheless, limited studies have compared genotypes for hay and silage quality in semi-arid Mediterranean environments. Producers and breeders in Türkiye’s Southeastern Anatolia (SA) Region region lack concurrent data linking biomass production with standardized feed-quality indices across various pearl millet [genotypes. This study addressed this gap by evaluating the qualitative attributes of hay and silage from 25 genotypes cultivated as a second crop during the summer season in Akçakale–Şanlıurfa (Mediterranean, semi-arid) in 2022. The primary objective was to identify high-performing candidate genotypes for semi-arid forage systems.Genotypes were evaluated for fodder and dry matter (DM) yield, as well as forage quality traits in pre-ensiled hay and silage produced after a 60-day fermentation period. Plants were harvested at the milk-dough stage, and forage yield, dry matter yield (DMY), and feed quality were assessed in both pre-ensiled and ensiled materials. Forage yield varied between 75.50 and 136.23 t ha⁻¹. Genotype 15836 had the maximum fodder production (136.23 t ha⁻¹), while genotypes 3642 and 1665 (75.50 and 75.55 t ha⁻¹, respectively) produced the lowest fodder yield. The DMY of tested genotypes varied between 24.70 and 45.14 t ha⁻¹. For hay and silage, crude protein ranged from 4.32% to 9.43% and 4.43% to 8.96%, respectively. Similarly,crude ash ranged from 6.44% to 10.80% and 5.29% to 9.89%. Likewise,neutral detergent fiber (NDF) ranged from 59.16% to 67.38% and 38.61% to 65.41%, whereas acid detergent fiber (ADF) ranged from 34.19% to 40.41% and 23.64% to 42.12%. In the same way, acid detergent lignin (ADL) ranged from 4.59% to 7.53% and 0.782% to 5.275%. Digestible dry matter (DDM) ranged from 57.42% to 62.17% for hay and from 56.09% to 70.49% for silage. Similarly, dry matter intake (DMI) varied between 1.791% and 2.028% and between 1.841% and 3.109%. Relative feed value (RFV) was between 79.99 and 96.42 and between 80.24 and 169.88. Silage materials demonstrated reduced fiber fractions and elevated DDM, DMI, and RFV across several genotypes, indicating improved intake potential and energy availability. Four genotypes (1566, 14522, 15836, 21438) consistently exhibited higher DM yield, although genotype 2346 produced the greatest silage RFV, with many others (1536, 1665, 7259, 8562) that also attained first-quality silage. These genotypes could reduce seasonal feed shortages and be used in the breeding programs for developing climate-resilient forage systems in semi-arid areas.
Keywords: Pearl Millet; Forage Yield; Feed Quality; Genotypes; Silage